KAITAN ANTARA STATUS GIZI, PERKEMBANGAN KOGNITIF, DAN PERKEMBANGAN MOTORIK PADA ANAK USIA PRASEKOLAH (RELATIONSHIP BETWEEN NUTRITIONAL STATUS, COGNITIVE DEVELOPMENT, AND MOTOR DEVELOPMENT IN PRESCHOOL CHILDREN) - Rindu Dwi Malateki Solihin; Faisal Anwar; Dadang Sukandar (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACT Growth failure (stunting) in children under five causes a variety of development disorders, including cognitive and motor development. The objective of this study was to analyze the relationship between nutritional status, cognitive development, and motor development in preschool children. This survey was conducted on 73 children aged 3-5 years in Bogor regency, West Java. This study showed that 30.2 percent children had low height for age. 98.6 percent children had normal birth weight and 76.7 percent children had normal birth length. Children’s level of cognitive (54.8%) and fine motor development (68.5%) were low, while gross motor development level were moderate (41.1%). Factors that significantly associated with children’s nutritional status were mother’s height, children’s energy and protein sufficiency level, and birth length of children. Factors that significantly associated with children’s fine and gross motor development were children’s nutritional status, early education, and age of children. Factors that significantly associated with children’s cognitive development were children’s nutritional status, age of children, early education, and children care practices of mother. Children’s nutrient sufficiency level, especially energy and protein, has significant association to their nutritional status and development Keywords: nutritional status, cognitive development, motor development, preschool children   ABSTRAK Kegagalan pertumbuhan (stunting) pada anak usia di bawah lima tahun (balita) dapat menyebabkan berbagai gangguan perkembangan, termasuk perkembangan kognitif dan motorik. Penelitian ini bertujuan untuk menganalisis kaitan antara status gizi, perkembangan kognitif dan motorik pada anak usia prasekolah. Penelitian berdesain survei ini dilakukan pada 73 anak usia 3-5 tahun di Desa Cibanteng, Kabupaten Bogor, Jawa Barat. Hasil penelitian menunjukkan bahwa sebanyak 30,2 persen anak balita berstatus gizi tergolong pendek, 98,6 persen anak memiliki berat badan lahir normal, dan 76,7 persen anak mempunyai panjang lahir normal. Tingkat perkembangan kognitif (54,8%) dan motorik halus (68,5%) anak tergolong rendah, sementara tingkat perkembangan motorik kasar anak tergolong sedang (41,1%). Faktor-faktor yang berhubungan signifikan dengan status gizi balita adalah tinggi badan ibu, tingkat kecukupan energi dan protein balita dan panjang badan lahir balita. Faktor-faktor yang berkaitan signifikan dengan tingkat perkembangan motorik kasar dan motorik halus balita adalah status gizi balita, lama mengikuti PAUD dan usia balita. Faktor-faktor yang berhubungan signifikan dengan tingkat perkembangan kognitif balita adalah status gizi balita, usia balita, lama mengikuti PAUD dan praktik pengasuhan balita oleh ibu. Tingkat kecukupan gizi balita, terutama energi dan protein, berhubungan dengan status gizi dan perkembangan mereka. [Penel Gizi Makan 2013, 36(1):62-72] Kata kunci: status gizi, perkembangan kognitif, perkembangan motorik, anak prasekolah